Processing and Characterization of Banana Fiber/Epoxy Composites: Effect of Alkaline Treatment - Muhammad Khusairy, Bin Bakri; Elammaran, Jayamani; Sinin, Hamdan (Elsevier Ltd., 2017)
This research focuses on the development of natural fibers reinforced polymer matrix composites using agricultural waste, such as banana fibers. The banana fibers were obtained from agricultural field after banana fruit has been matured. And it underwent an alkaline treatment using 5wt% of sodium hydroxide. The composites were prepared with various fiber loadings, ranging from 5wt%, to 20wt%. The effects of alkaline treatment on the mechanical, morphological, and spectral properties were investigated and evaluated using, universal testing machine, light/optical microscope, scanning electron microscopy, and Fourier transform infrared spectroscopy. Based on the results obtained, it is noticed that a lot of factors involved in affecting the characteristics of the natural composites, such as density, fiber amount, structure agglomeration and etc. From the results obtained, treated fiber composites have superior properties as compared with untreated fiber composites.